Youth sport research: Describing the integrated dynamic elements of the personal assets framework - Côté, J.; Turnnidge, J.; Murata, A.; Mcguire, C. S.; Martin, L. J. (International Journal of Sport Psychology, 2020)
This critical review of the youth sport literature provides a guiding framework to inform future studies and interventions aimed at understanding or manipulating mechanisms proposed to explain youth athlete development. A global vision of athlete development is presented through the interactions of three dynamic elements: (1) appropriate settings, (2) quality social dynamics, and (3) personal engagement in activities. These elements are further broken down into individual layers, extending proximally to distally with layers positioned closest to an athlete having the most immediate impact. Given the correct arrangement, these dynamic elements work in concert to foster immediate, short-term, and long-term outcomes related to development in sport. We provide a detailed description of each dynamic element and include example literature associated with each of the subsequent layers.